Antigiardial Activity of Acetylsalicylic Acid Is Associated with Overexpression of HSP70 and Membrane Transporters - Verónica Yadira Ochoa-Maganda; Itzia Azucena Rangel-Castañeda; Daniel Osmar Suárez-Rico; Rafael Cortés-Zárate; José Manuel Hernández-Hernández; Armando Pérez-Rangel; Natalia Chiquete-Félix; Gloria León-Ávila; Sirenia González-Pozos; Jorge Gaona-Bernal; Araceli Castillo-Romero (MDPI AG, 2020)
Giardia lamblia is a flagellated protozoan responsible for giardiasis, a worldwide diarrheal disease. The adverse effects of the pharmacological treatments and the appearance of drug resistance have increased the rate of therapeutic failures. In the search for alternative therapeutics, drug repositioning has become a popular strategy. Acetylsalicylic acid (ASA) exhibits diverse biological activities through multiple mechanisms. However, the full spectrum of its activities is incompletely understood. In this study we show that ASA displayed direct antigiardial activity and affected the adhesion and growth of trophozoites in a time-dose-dependent manner. Electron microscopy images revealed remarkable morphological alterations in the membrane, ventral disk, and caudal region. Using mass spectrometry and real-time quantitative reverse transcription (qRT-PCR), we identified that ASA induced the overexpression of heat shock protein 70 (HSP70). ASA also showed a significant increase of five ATP-binding cassette (ABC) transporters (giABC, giABCP, giMDRP, giMRPL and giMDRAP1). Additionally, we found low toxicity on Caco-2 cells. Taken together, these results suggest an important role of HSPs and ABC drug transporters in contributing to stress tolerance and protecting cells from ASA-induced stress.